2023
DOI: 10.1055/s-0043-1762901
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Resolution of a Humeral Intracondylar Fissure in a Skeletally Immature French Bulldog

Abstract: A 4-month-old male entire French bulldog was presented for the investigation of acute left thoracic limb lameness. Computed tomography (CT) revealed a right-sided humeral intracondylar fissure (HIF) and a left-sided medial humeral condylar fracture which was managed by open reduction and internal fixation. Follow-up CT at 36 days after surgery revealed healing of the condylar fracture and partial resolution of the HIF, which was radiographically unapparent on further CT images 105 days thereafter (at 220 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…14,27 However, there exists a single case report of a spontaneous resolution of an HIF in a very young French Bulldog puppy. 28 Although this report suggests a possibility of spontaneous healing, it is crucial to acknowledge that the tendency of these defects is typically not to heal. Furthermore, given the age of the animal in the mentioned case, the presence of a definitive HIF diagnosis might be questionable.…”
Section: Discussionmentioning
confidence: 83%
“…14,27 However, there exists a single case report of a spontaneous resolution of an HIF in a very young French Bulldog puppy. 28 Although this report suggests a possibility of spontaneous healing, it is crucial to acknowledge that the tendency of these defects is typically not to heal. Furthermore, given the age of the animal in the mentioned case, the presence of a definitive HIF diagnosis might be questionable.…”
Section: Discussionmentioning
confidence: 83%
“…25 A recent case report of a single case suggests spontaneous resolution of humeral intracondylar fissure can occur in this breed. 26 This present study suggests that no specific fixation method carries a higher risk for postoperative complications in medial or lateral fractures of the humeral condyle (p ¼ 0.87). This contrasts with another study which reported a notable increase in complication rate in elbows stabilized with a transcondylar screw and Kirschner wires rather than those with an epicondylar plate.…”
Section: Discussionmentioning
confidence: 60%
“…25 A recent case report of a single case suggests spontaneous resolution of humeral intracondylar fissure can occur in this breed. 26…”
Section: Discussionmentioning
confidence: 99%